On the dynamic response of square tunnels in sand. (15th October 2016) - Tsinidis, Grigorios; Pitilakis, Kyriazis; Madabhushi, Gopal
Highlights: Dynamic centrifuge tests are performed on square tunnels in dry sand. The test cases are analyzed by means of full dynamic analysis. Results indicate a rocking deformation mode coupled with racking distortion. Interface conditions and soil yielding affect significantly the response. The effect of the lining rigidity on the response is highlighted. Abstract: The paper investigates the seismic response of square tunnels in sand by means of dynamic centrifuge testing and numerical analysis. A series of dynamic centrifuge tests, conducted at the University of Cambridge on a square aluminium model tunnel embedded in dry sand, are initially presented. The tests, which were designed to investigate the seismic response of flexible tunnels, are analyzed numerically by means of full dynamic analysis of the coupled soil-tunnel system, using different soil and soil-tunnel interface models. Numerical predictions are compared to the experimental data, so as to better understand the response mechanism and validate the numerical modelling. The validated numerical models are then used to investigate the effect of lining rigidity on the soil-tunnel system dynamic response. The experimental and numerical results reported herein, indicate a non-negligible rocking deformation mode for the tunnels during seismic shaking coupled with racking distortion. The significant effects of the lining rigidity, soil-tunnel interface characteristics and soil yielding on the dynamic earth pressures and the shear stresses developed around the perimeter of the tunnel, as well as on the dynamic lining forces, are also reported and discussed.